Assessing the taxonomic status of Amanita citrina var. intermedia (Basidiomycota, Agaricales) - Vizzini, Alfredo; Cingarlini, Claudio; Sartori, Daniele; Maraia, Gian Luigi; Setti, Ledo; Poumarat, Serge; Kudzma, Linas; Dovana, Francesco (Phytotaxa, 2020)
Multigene molecular analysis (nrITS, nrLSU, tef1, rpb2) of Amanita species of section Validae including Italian and French specimens of A. citrina var. intermedia indicates that the taxon is not conspecific with A. mappa (= A. citrina) and deserves to be upgraded to the rank of autonomous species. An in-depth description of the taxon, a comparison with allied species, and a key to the Amanita species of section Validae series Mappae in Europe, are provided.